The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1007/s0033501-0005-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conservation, developmental expression, and genomic mapping of mammalian Twisted gastrulation

Abstract: The twisted gastrulation gene (tsg) encodes a secreted protein required for the correct specification of dorsal midline cell fate during gastrulation in Drosophila. We report that tsg homologs from human, mouse, zebrafish, and Xenopus share 72-98% identity at the amino acid level and retain all 24 cysteine residues from Drosophila. In contrast to Drosophila where tsg expression is limited to early embryos, expression is found throughout mouse and human development. In Drosophila, tsg acts in synergy with decap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…47 BMP7 is produced by the distal tubule and collecting duct, 11,19 whereas CHRDL1 is secreted by the adjacent proximal tubule (Figures 2 and 3), establishing opposing gradients of these two proteins. Both in situ hybridization 20,35 and immunostaining ( Figure 4E) assays indicate that Twsg1 is expressed in the renal epithelia. Thus, it is anticipated that the proximal tubule of the healthy kidney is subject to the greatest BMP7 antagonism by CHRDL1/ TWSG1.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…47 BMP7 is produced by the distal tubule and collecting duct, 11,19 whereas CHRDL1 is secreted by the adjacent proximal tubule (Figures 2 and 3), establishing opposing gradients of these two proteins. Both in situ hybridization 20,35 and immunostaining ( Figure 4E) assays indicate that Twsg1 is expressed in the renal epithelia. Thus, it is anticipated that the proximal tubule of the healthy kidney is subject to the greatest BMP7 antagonism by CHRDL1/ TWSG1.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies showed ubiquitous Twsg1 expression in the kidney, with the highest expression in outer medulla. 20,35 TWSG1 protein expression was confirmed by immunostaining in both mouse and human kidney. In both species, protein expression is strong in proximal and other tubule epithelia and weak in interstitial cells and glomeruli ( Figure 4E).…”
Section: Chrdl1 Alone Amplifies Bmp4 and 7 Signaling But Selectively mentioning
confidence: 86%
“…The twisted gastrulation (tsg ) invertebrate gene (Mason et al, 1994) has an equivalent gene family in vertebrates (mammalian tsg ) (Graf et al, 2001). Recently we investigated the expression of CCN3 during early embryogenesis (Katsube et al, 2001).…”
Section: Novel Ccn Molecules Which Regulate Notch Signaling Were Creamentioning
confidence: 99%
“…Mouse Tsg is expressed during lymphocyte development (22), and Chordin (23), BMP4 (24), and the Smad-interacting transcription factor Schnurri-2 (25) are expressed in the mouse thymus, suggesting that BMP signaling may play a role in thymocyte development.…”
mentioning
confidence: 99%